"Tag-Team" Orbital and Strabismus Surgeries with Immediate Reconstruction After Tumor Excision Metastatic to the Inferior Rectus. Issue 1 (January 2016) - Wu, Chris Y.; Archer, Steven M.; Kahana, Alon
Abstract : Carcinoid tumors are rare, slow-growing, low-grade neuroendocrine tumors with a propensity for orbital metastatic spread. The typical treatment paradigm for localized orbital disease involves excision, adjuvant radiotherapy, and/or receptor-targeted chemotherapy, followed by delayed evaluation for reconstructive strabismus surgery. We present a 58-year-old female patient with carcinoid tumor metastatic to the right inferior rectus muscle who presented with worsening binocular diplopia. The patient underwent coordinated "tag-team" orbital and strabismus surgeries that included excision of the right inferior rectus muscle to the annulus of Zinn followed immediately by reconstructive strabismus surgery. The patient required 1 additional strabismus surgery 1 year later. Follow up revealed no tumor recurrence at 4 years, and excellent binocular vision with good function. Deep orbital and strabismus surgeries, when performed simultaneously in a "tag-team" approach, may offer superior functional outcomes and improved patient quality of life, with expedited functional recovery. This approach may become a new treatment paradigm for surgical disease processes localized to the extraocular muscles.